La dynamique du marché immobilier de la ville de Buenos Aires. Le cas de « Las Cañitas » (1991-2018) - Adrián C. Iulita (Confins)
The advent of the civic-military dictatorship in 1976 inaugurated a new stage in the form of "making city" in Argentina, and particularly in the Autonomous City of Buenos Aires (CABA). In the present work, we approach the case of "Las Cañitas", an area of ten blocks between the neighborhoods of Palermo and Belgrano, north of the Autonomous City of Buenos Aires, which have mutated from this "new" way of making a city, both in its social and urban structure. We analyze the processes that allowed the emergence of this "exclusive area" within the city, from its configuration as a "fashionable gastronomic pole" during the 1990s and, after the deep crisis of 2001, its positioning as a privileged object within of the real estate market in the city.